Rewriting the Book of Nature: Kabbalah and the Metaphors of Contemporary Life Sciences - Stuckrad, Kocku von (Journal for the Study of Religion, Nature and Culture, 2009)
At the beginning of the twenty-first century, it seems as if biology, genetics, and the ‘life sciences’ are in normative control of cultural discourses regarding nature, the body, and the cosmos. This article addresses religious and esoteric semantics that underlie modern biology. The ‘deciphering’ of the human genetic ‘code’—a metaphor introduced to the ‘life sciences’ by Erwin Schrödinger in 1944—rests on Pythagorean and kabbalistic notions about letters and numbers as the building blocks of the cosmos. The progress of ‘genetic engineering’ and related techniques puts the human being into the position of universal creator of life. The philosophical interest in natura naturans returns in modern science in an unambiguously religious and metaphysical way. Looking at the kabbalistic tradition and its ‘ontologization’ of language and letters reveals the genealogy of conceptual frameworks that are still operative today.